Susceptibility to multitasking in stroke is associated to multiple-demand system damage and leads to lateralized visuospatial deficits - Elvio Blini; Daniela D’Imperio; Zaira Romeo; Michele De Filippo De Grazia; Laura Passarini; Cristina Pilosio; Francesca Meneghello; Mario Bonato; Marco Zorzi (Communications Biology)
Abstract Cognitive impairment after stroke is heterogeneous: there is no strict correspondence between brain damage and magnitude of deficit or recovery. Protective factors such as cognitive or brain reserve have been invoked to explain the mismatch. Here, we consider the opposite point of view: the instances in which this protection is overturned. We leveraged on multitasking to stress the brain’s processing limits and unveil deficits that may be missed by standard testing in a sample of 46 patients with unilateral subacute to chronic stroke and no sign of lateralized spatial-attentional disorders at neuropsychological paper-and-pencil tests. Multivariate analyses identified a phenotype of patients with high susceptibility to multitasking, showing stark contralesional spatial awareness deficit only when multitasking. Multivariate brain-behavior mapping based on lesions location and structural disconnections pointed to the Multiple-Demand System, a network of frontal and fronto-parietal areas subserving domain-general processes. Damage in this network may critically interact with domain-specific processes, resulting in subtle and yet invalidating deficits. Indeed, these patients (one-third of the sample) presented worse performance in tests evaluating activities of daily living and domain-general abilities. We conclude that the theoretical construct of susceptibility to multitasking helps understanding what marks the passage to clinically visible deficits after brain damage.